Cobaltosic oxide, preparation method thereof, lithium cobalt oxide, positive pole piece and battery

By controlling the preparation process and calcining conditions of cobalt carbonate, cobalt tetroxide with high sintering activity and mechanical strength was prepared, which solved the problem of improper control of particle size and grain size in the prior art, and improved the electrochemical performance and mechanical properties of lithium cobalt oxide. performance.

CN119118214AActive Publication Date: 2024-12-13GUANGDONG BRUNP RECYCLING TECH CO LTD +1

Patent Information

Application Number
CN202411587551.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2024-12-13
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The improper control of the existing particle size and grain size of cobalt tetroxide makes it difficult to take into account both its mechanical strength and sintering activity, affecting the morphology and electrochemical properties of lithium cobalt oxide.

Method used

By controlling the preparation process of cobalt carbonate, including adjusting its crystallinity and particle size, pre-sintering and calcining with a flash dryer, ensuring that the grain size and specific surface area of ​​the (111) crystal surface of cobalt tetroxide are within a suitable range, combined with suitable By calcining conditions, cobalt tetroxide with high sintering activity and mechanical strength was prepared.

Benefits of technology

The high reactivity and mechanical properties of cobalt tetroxide and lithium source are achieved, the lithium ion diffusion rate and first charge and discharge efficiency of lithium cobalt oxide are improved, and the high specific capacity and good electrochemical performance are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118214A_ABST
    Figure CN119118214A_ABST
Patent Text Reader

Abstract

The invention discloses cobaltosic oxide, a preparation method thereof, lithium cobalt oxide, a positive pole piece and a battery, and relates to the technical field of lithium battery positive pole materials. The Dv50 of the cobaltosic oxide, the grain size D (111) of the (111) crystal face and the specific surface area BET meet the following relation: 3.33 [mu] m < 3 > / g < = # imgabs0 # < = 6.90 [mu] m < 3 > / g, wherein the Dv50 of the cobaltosic oxide is 3-20 [mu] m. The cobaltosic oxide is obtained by pre-sintering and calcining cobalt carbonate with the crystallinity of 30%-80% and the median particle size Dv50 of 3-22 [mu] m; the reaction activity of the cobaltosic oxide and a lithium source is high, the mechanical property is good, the lithium ion diffusion rate of the obtained lithium cobalt oxide is high, and the specific capacity and the first charge-discharge efficiency are relatively high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of positive electrode materials for lithium batteries, and in particular to cobalt tetroxide and a preparation method thereof, lithium cobalt oxide, a positive electrode sheet and a battery. Background Art

[0002] Lithium cobalt oxide positive electrode materials are widely used in the 3C field due to their high energy density, good cycle and rate performance. With the hot sales of emerging electronic products such as drones, electric toys, VR glasses, etc., the market for consumer lithium cobalt oxide has been further driven.

[0003] Cobalt tetroxide is an important precursor material for the preparation of lithium cobalt oxide. Its physical forms such as morphology, structure, grain size, and particle size will continue into the lithium cobalt oxide positive electrode material and have a great influence on its electrochemical properties. For example, the larger the specific surface area of ​​cobalt tetroxide, the more active sites there are during the sintering of cobalt tetroxide and lithium source, the greater the sintering activity, and the higher the crystallinity of the obtained lithium cobalt oxide, which is beneficial to improving the specific capacity of the positive electrode material. The specific surface area of ​​cobalt oxide is related to multiple factors, such as particle size, crystal size, porosity of secondary particles, etc.; generally, the smaller the particle size, the smaller the grain size, and the larger the porosity of cobalt oxide, the larger the specific surface area; but too small particle size and / or small grain size and / or too large porosity will lead to decreased mechanical strength of particles, resulting in cracking and pulverization in subsequent processing, thereby affecting the morphology and performance of lithium cobalt oxide; therefore, controlling the particle size, crystal size and specific surface area of ​​cobalt oxide within an appropriate range is conducive to obtaining a lithium cobalt oxide precursor with good sintering activity and mechanical properties, and the subsequently obtained lithium cobalt oxide has a uniform morphology and good electrochemical properties.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a cobalt tetroxide and a preparation method thereof, lithium cobalt oxide, a positive electrode plate and a battery, aiming to provide a cobalt tetroxide with high sintering activity and high mechanical strength, and the lithium cobalt oxide prepared using the cobalt tetroxide as a precursor has a high specific capacity and initial charge and discharge efficiency.

[0006] The present invention is achieved in that: In a first aspect, the present invention provides a cobalt oxide having the following characteristics: the Dv50 of the cobalt oxide, the grain size D(111) of the (111) crystal plane, and the specific surface area BET satisfy the following relationship: 3.33 μm 3 / g≤ ≤6.90μm 3 / g; wherein the Dv50 of the cobalt tetroxide is 3-20 μm, Dv50 refers to the particle size corresponding to 50% of the cumulative particle size distribution based on volume statistics, and the unit of BET is m2 / g, the unit of D(111) is μm, The unit is μm 3 .

[0007] In some embodiments, the grain size D(111) of the cobalt oxide (111) crystal plane is 0.0450-0.0510 μm or 0.0560-0.0680 μm.

[0008] In some embodiments, the specific surface area of ​​the cobalt oxide is 2 to 6.5 m 2 / g.

[0009] In some embodiments, the particle size broadening coefficient Span of the cobalt tetroxide is less than 1, wherein Span=(Dv90-Dv10) / Dv50, Dv10, Dv50, and Dv90 refer to the particle sizes corresponding to 10%, 50%, and 90% of the cumulative particle size distribution based on volume statistics; preferably, Span is 0.35~0.70.

[0010] In some embodiments, the change rate of Dv50 of the cobalt tetroxide after 7500N pressing relative to that before pressing is Less than 2.0%; preferably, 0.58%~1.65%; among them, D%=(Dv50-Dv50') / Dv50×100%,Dv50 and Dv50' are the median particle sizes of the material particles before and after pressing, respectively.

[0011] In some embodiments, the grain size D(111) of the (111) crystal plane of cobalt oxide is 0.0450-0.0510 μm, and the median particle size Dv50 is 3-6 μm.

[0012] In some embodiments, the grain size D(111) of the (111) crystal plane of cobalt oxide is 0.0560-0.0680 μm, and the median particle size Dv50 is 16-20 μm.

[0013] In a second aspect, the present invention provides a method for preparing cobalt tetroxide, which has the following characteristics: the cobalt tetroxide is obtained by pre-sintering and calcining cobalt carbonate having a crystallinity of 30% to 80% and a median particle size Dv50 of 3 to 22 μm.

[0014] In some embodiments of the present invention, the preparation method of cobalt carbonate is as follows: a cobalt salt solution and a precipitant solution are added to a reactor containing a bottom liquid in parallel, stirring is started at the same time to react until the material in the reactor reaches the upper limit, the addition and stirring are stopped, the material is allowed to stand for sedimentation, part of the supernatant is extracted, the above-mentioned addition and stirring, standing, and part of the supernatant are extracted, until the obtained cobalt carbonate reaches the target particle size, and the solid is washed after solid-liquid separation.

[0015] In some embodiments of the present invention, the method for preparing cobalt carbonate further comprises at least one of the following features: Feature 1: The cobalt salt in the cobalt salt solution is at least one of cobalt chloride, cobalt sulfate and cobalt nitrate, and the concentration of the cobalt salt solution is 2.0-2.5 mol / L; Feature 2: The precipitant in the precipitant solution is at least one of sodium carbonate, sodium bicarbonate, ammonium bicarbonate and potassium carbonate, and the concentration of the precipitant solution is 1.0-3.0 mol / L; Feature 3: The flow rate of adding the cobalt salt solution is 20-40 L / h, and the flow rate of adding the precipitant solution is 20-30 L / h; Feature 4: The base liquid is the precipitant solution; Feature 5: The stirring speed is 200-300 rpm, and the reaction temperature is 40-55°C; Feature 6: Extracting part of the supernatant means extracting the supernatant equivalent to half of the volume of the reactor chamber; Feature 7: The target particle size refers to the median particle size Dv50 of cobalt carbonate being 3 to 22 μm.

[0016] In some embodiments of the present invention, the pre-sintering adopts a flash dryer; the inlet air temperature of the flash dryer is 300-400°C, the outlet air temperature is 150-180°C, the main engine speed is 20-30Hz, and the feed frequency is 10-20Hz.

[0017] In some embodiments of the present invention, the calcination is carried out in a rotary kiln, the feed frequency of the rotary kiln is 3-9 Hz, the rotation frequency of the furnace tube is 12-15 Hz, the temperature is 710-760° C., and the calcination time is 3-5 h.

[0018] In a third aspect, the present invention provides a lithium cobalt oxide, which is obtained by mixing the cobalt trioxide obtained in any of the above embodiments with a lithium source and sintering them.

[0019] In a fourth aspect, the present invention provides a positive electrode plate, wherein the positive electrode plate comprises the lithium cobalt oxide of the third aspect.

[0020] Furthermore, the present invention also provides a battery, comprising the positive electrode plate of the fourth aspect.

[0021] The present invention has the following beneficial effects: (1) The cobalt oxide provided by the present invention has a suitable grain size of the (111) crystal plane, so it has high reactivity with lithium sources and good mechanical properties. The lithium cobalt oxide obtained has a high lithium ion diffusion rate, and thus has a high specific capacity and initial charge and discharge efficiency.

[0022] (2) The present invention controls the preparation process of cobalt carbonate to obtain cobalt carbonate with specific crystallinity and particle size, so as to achieve both good sintering activity and mechanical strength. The cobalt carbonate is further pre-sintered in a flash dryer to shrink its volume instantly, and the stirring during the flash evaporation process is used to achieve deagglomeration, so that the final cobalt tetroxide has good dispersibility and high particle integrity. The calcination conditions are further controlled so that the grain size of the (111) crystal plane of the obtained cobalt tetroxide is within an appropriate range. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0024] Figure 1 This is a SEM image of the cobalt tetroxide prepared in Example 1; Figure 2 This is a SEM image of the cobalt tetroxide prepared in Example 6; Figure 3 This is a SEM image of cobalt tetroxide prepared in Comparative Example 1; Figure 4 This is a SEM image of cobalt tetroxide prepared in Comparative Example 2; Figure 5 This is the XRD pattern of the cobalt tetroxide prepared in Example 1; Figure 6 This is the XRD pattern of the cobalt tetroxide prepared in Example 6; Figure 7 This is the XRD pattern of cobalt tetroxide prepared in Comparative Example 1; Figure 8 This is the XRD pattern of cobalt tetroxide prepared in Comparative Example 2. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0026] The present invention provides a cobalt tetraoxide having the following characteristics: Dv50, grain size D(111) of the (111) crystal plane, and specific surface area BET of the cobalt tetraoxide satisfy the following relationship: 3.33 μm 3 / g≤ ≤6.90μm 3 / g; wherein the Dv50 of the cobalt tetroxide is 3-20 μm, Dv50 refers to the particle size corresponding to 50% of the cumulative particle size distribution based on volume statistics, and the unit of BET is m 2 / g, the unit of D(111) is μm, The unit is μm 3 .

[0027] The diffraction angle corresponding to the (111) crystal plane of cobalt tetroxide in the XRD spectrum is 2 =18~20°.

[0028] The grain size D(111) of the cobalt oxide (111) crystal plane is obtained by X-ray diffraction (XRD) spectrum analysis, and is calculated by obtaining the diffraction angle and half-width (FWHM) corresponding to the diffraction peak of the (111) crystal plane and using the Scherrer formula.

[0029] Cobalt tetroxide is an important precursor material for the preparation of lithium cobalt oxide. Its physical forms such as morphology, structure, grain size, and particle size will continue into the lithium cobalt oxide positive electrode material and have a great influence on its electrochemical properties. For example, the larger the specific surface area of ​​cobalt tetroxide, the more active sites there are during the sintering of cobalt tetroxide and lithium source, the greater the sintering activity, and the higher the crystallinity of the obtained lithium cobalt oxide, which is beneficial to improving the specific capacity of the positive electrode material. The specific surface area of ​​cobalt oxide is related to multiple factors, such as particle size, crystal size, porosity of secondary particles, etc.; generally, the smaller the particle size and crystal size of cobalt oxide, the larger the porosity and the larger the specific surface area; but too small particle size and / or crystal size and / or porosity will lead to decreased mechanical strength of particles, resulting in cracking and pulverization in subsequent processing, thus affecting the morphology and performance of lithium cobalt oxide; therefore, controlling the particle size, crystal size and specific surface area of ​​cobalt oxide within an appropriate range is conducive to obtaining a lithium cobalt oxide precursor with good sintering activity and mechanical properties, and the subsequently obtained lithium cobalt oxide has a uniform morphology and good electrochemical properties.

[0030] The cobalt oxide material provided by the present invention satisfies the above value range and has good sintering activity and mechanical strength, and the subsequently obtained lithium cobalt oxide has good lithium ion diffusion efficiency.

[0031] In some embodiments of the present invention, the grain size D(111) of the cobalt oxide (111) crystal plane is 0.0450-0.0510 μm or 0.0560-0.0680 μm.

[0032] In some embodiments of the present invention, the specific surface area of ​​the cobalt oxide is 2 to 6.5 m 2 / g.

[0033] In some embodiments of the present invention, the particle size broadening coefficient Span of the cobalt oxide is less than 1, wherein Span=(Dv90-Dv10) / Dv50, Dv10, Dv50, and Dv90 refer to the particle sizes corresponding to 10%, 50%, and 90% of the cumulative particle size distribution based on volume statistics; preferably, Span is 0.35~0.70.

[0034] The particle size broadening coefficient Span reflects the uniformity of the particle size of cobalt oxide particles. The cobalt oxide provided by the present invention has a lower Span, indicating that its degree of agglomeration is lower. The lower degree of agglomeration is beneficial to improving the mixed sintering of the cobalt oxide with the lithium source. The obtained lithium cobalt oxide has a more uniform particle size distribution and a higher crystal phase purity, which is beneficial to providing the electrochemical properties of the lithium cobalt oxide.

[0035] In some embodiments of the present invention, the change rate of Dv50 of the cobalt tetroxide after 7500N pressing relative to that before pressing is Less than 2.0%; preferably, 0.58%~1.65%; among them, D%=(Dv50-Dv50') / Dv50×100%,Dv50 and Dv50' are the median particle sizes of the material particles before and after pressing, respectively.

[0036] Dv50 change rate The compressive strength of cobalt tetroxide can be evaluated. Specifically, the higher the compressive strength of cobalt tetroxide, the The smaller it is, the less likely it is to have particle breakage and powder shedding during subsequent mixed sintering with the lithium source.

[0037] In some embodiments of the present invention, the grain size D(111) of the (111) crystal plane of cobalt oxide is 0.0450-0.0510 μm, and the median particle size Dv50 is 3-6 μm.

[0038] In some embodiments of the present invention, the grain size D(111) of the (111) crystal plane of cobalt oxide is 0.0560-0.0680 μm, and the median particle size Dv50 is 12-20 μm.

[0039] In a second aspect, the present invention provides a method for preparing cobalt tetroxide, which has the following characteristics: Cobalt trioxide is obtained by pre-sintering and calcining cobalt carbonate with a crystallinity of 30% to 80% and a median particle size Dv50 of 3 to 22 μm.

[0040] The present invention uses cobalt carbonate with specific crystallinity and particle size to prepare cobalt tetroxide, so that the cobalt carbonate has high sintering activity and good mechanical strength, which can prevent the particles from losing powder and being damaged on the surface during the flash drying and deagglomeration process. In addition, cobalt carbonate with specific crystallinity and particle size can be obtained by pre-sintering and calcining to meet the 3.33μm 3 / g≤ ≤6.90μm 3 / g of cobalt tetroxide.

[0041] In some embodiments of the present invention, cobalt carbonate having a crystallinity of 50% to 80% and a median particle size Dv50 of 3 to 7 μm is pre-sintered and calcined to obtain cobalt tetroxide having a grain size D(111) of 0.0450 to 0.0510 μm on the (111) crystal plane and a median particle size Dv50 of 3 to 6 μm.

[0042] In some embodiments of the present invention, cobalt carbonate having a crystallinity of 30% to 65% and a median particle size Dv50 of 13 to 22 μm is pre-sintered and calcined to obtain cobalt tetroxide having a grain size D(111) of 0.0560 to 0.0680 μm on the (111) crystal plane and a median particle size Dv50 of 12 to 20 μm.

[0043] In some embodiments of the present invention, the preparation method of cobalt carbonate is as follows: a cobalt salt solution and a precipitant solution are added to a reactor containing a bottom liquid in parallel, stirring is started at the same time to react until the material in the reactor reaches the upper limit, the addition and stirring are stopped, the material is allowed to stand for sedimentation, part of the supernatant is extracted, the above-mentioned addition and stirring, standing, and part of the supernatant are extracted, until the obtained cobalt carbonate reaches the target particle size, and the solid is taken for washing after solid-liquid separation.

[0044] In some embodiments of the present invention, the method for preparing cobalt carbonate further comprises at least one of the following features: Feature 1: The cobalt salt in the cobalt salt solution is at least one of cobalt chloride, cobalt sulfate and cobalt nitrate, and the concentration of the cobalt salt solution is 2.0-2.5 mol / L; Feature 2: The precipitant in the precipitant solution is at least one of sodium carbonate, sodium bicarbonate, ammonium bicarbonate and potassium carbonate, and the concentration of the precipitant solution is 1.0-3.0 mol / L; Feature 3: The flow rate of adding the cobalt salt solution is 20-40 L / h, and the flow rate of adding the precipitant solution is 20-30 L / h; Feature 4: The base liquid is the precipitant solution; Feature 5: The stirring speed is 200-300 rpm, and the reaction temperature is 40-55°C; Feature 6: Extracting part of the supernatant means extracting the supernatant equivalent to half of the volume of the reactor chamber; Feature 7: The target particle size refers to the median particle size Dv50 of cobalt carbonate being 3 to 22 μm.

[0045] The invention can obtain cobalt carbonate with specific crystallinity and particle size by adjusting the preparation process of cobalt carbonate.

[0046] In some embodiments of the present invention, the pre-sintering adopts a flash dryer; the inlet air temperature of the flash dryer is set to 300-400°C, the outlet air temperature is set to 150-180°C, the main engine speed is set to 20-30Hz, and the feed frequency is set to 10-20Hz.

[0047] The present invention sends the washed cobalt carbonate into a flash dryer for drying and pre-sintering. The particles shrink instantly under high heat, which reduces the interface between the agglomerated particles. At the same time, the stirring blades of the flash dryer further destroy the interface between the agglomerated particles, thereby achieving the purpose of deagglomeration, dispersing the particles individually, and improving the consistency of the particles.

[0048] In some embodiments of the present invention, the calcination is carried out in a rotary kiln, the feeding frequency is 3-9 Hz, the furnace tube rotation frequency is 12-15 Hz, the calcination time is 3-5 h, and the calcination temperature is 710-760° C.

[0049] The present invention controls the grain size corresponding to the (111) crystal plane of cobalt tetroxide to be within an appropriate range by controlling the calcination temperature and the calcination time.

[0050] In a third aspect, the present invention provides a lithium cobaltate obtained by mixing the cobalt trioxide obtained in any one of the above embodiments with a lithium source and sintering them.

[0051] In an optional embodiment, the lithium source includes at least one of lithium carbonate and lithium hydroxide.

[0052] In a fourth aspect, the present invention provides a positive electrode plate, wherein the positive electrode plate comprises the lithium cobalt oxide of the third aspect.

[0053] Furthermore, the positive electrode sheet is used to prepare a battery.

[0054] An embodiment of the present invention further provides a lithium battery, including the above-mentioned positive electrode plate, and may also include a negative electrode plate, an electrolyte, a separator, etc., to form a complete battery structure.

[0055] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0056] The test of the present invention is as follows: (1) X-ray diffraction (XRD): The present invention uses an energy dispersive X-ray diffractometer to perform XRD tests on the prepared cobalt carbonate and cobalt oxide. The test uses Cu Kα rays with a wavelength of 1.54056Å, a scanning angle of 10-68°, and a scanning speed of 3° / min. The XRD test results are analyzed using Jade 6 software, and the full spectrum is fitted and R is refined. wp ≤9%(R wp is the residual variance factor of the weighted graph, which can ensure the accuracy of refinement). The diffraction peak with a half-height width greater than 3° is an amorphous peak, and the diffraction peak with a half-height width less than 3° is a crystalline peak. The crystallinity of cobalt carbonate is calculated as follows: the sum of the peak areas of all crystalline peaks / the total area of ​​all peaks*100%; the grain size corresponding to the (111) crystal plane of cobalt tetroxide is calculated as follows: according to the diffraction angle of the (111) crystal plane ( ) and the half-height width of the diffraction peak ( ) and calculated according to the Scherrer formula: ; k is a constant value, the value is 0.9; Refers to the wavelength of the incident ray. When this formula is used to calculate the grain size, the half-height width of the diffraction peak ( ) are converted to radians for calculation.

[0057] (2) Particle size and distribution: The present invention uses a Malvern 3000 laser particle size analyzer to test the particle size and distribution of the prepared cobalt carbonate and cobalt oxide.

[0058] (3) Scanning electron microscopy (SEM): The present invention uses a field emission scanning electron microscope to observe and analyze the surface morphology of cobalt oxide.

[0059] (4) Particle size Dv50 change rate ( D%): The present invention adopts a powder compaction density instrument for testing, and the particle size Dv50 change rate ( D%) evaluates the compressive strength of material particles, D%=(Dv50-Dv50') / Dv50×100%,where Dv50 and Dv50' are the median particle sizes of the material particles before and after pressing, respectively. The pressing pressure is 7500N.

[0060] (5) Charge and discharge test: A button cell was assembled with lithium cobalt oxide as the positive electrode material for charge and discharge test. The test temperature was 25°C, the voltage range was 3.0~4.50V, and the rate was 0.1C. Specifically, the assembly of the button cell included the following steps: ① Preparation of lithium cobalt oxide: Cobalt tetroxide and lithium carbonate were mixed according to n(Co):n(Li) of 1:1.05, ground, dried, calcined at 1050°C for 30h, crushed, sieved to obtain lithium cobalt oxide; ② Preparation of positive electrode sheet: Lithium cobalt oxide: acetylene black: PVDF was prepared in a mass ratio of 75:15:10 to form a uniform slurry, uniformly coated on an aluminum foil substrate and dried; ③ Battery equipment: The electrolyte was 1 mol / L LiPF6 solution, and the solvent was a mixed solvent of EC and DMC in a volume ratio of 1:1; the negative electrode was graphite; the positive electrode, negative electrode, electrolyte, and diaphragm were assembled into a battery in an argon-protected glove box.

[0061] The XRD spectra of the cobalt tetraoxide prepared in Example 1, Example 6, Comparative Examples 1 and 2 of the present invention are shown in the attached specification. Figures 5 to 8 As shown in the figure, it can be seen that the present invention successfully prepares cobalt tetroxide, and the grain size of the (111) crystal plane can be calculated based on the diffraction angle and half-height width of the crystal plane in the XRD spectrum.

[0062] Example 1 A method for preparing cobalt trioxide comprises the following steps: (1) 100 L of 1.5 mol / L sodium carbonate solution was added to a reactor as a base liquid, and a 2.0 mol / L cobalt chloride solution was added to the reactor at a rate of 20 L / h and a 1.5 mol / L sodium carbonate solution was added to the reactor at a rate of 30 L / h, and stirring was started and the speed was adjusted to 300 rpm, and the temperature was adjusted to 40°C for reaction; when the material in the reactor reached the upper limit, the feeding and stirring were stopped, and the material was allowed to stand until the material was completely settled; a supernatant equivalent to half of the reactor cavity volume was extracted; then the cobalt chloride solution and sodium carbonate solution were added to the reactor in parallel and stirring was started for reaction, and the above-mentioned standing, extracting part of the supernatant, and feeding operations were repeated 8 times to obtain cobalt carbonate with a median particle size Dv50 of 4.0 μm; the cobalt carbonate was filtered in a centrifuge and washed with pure water 3 times to obtain a filter cake; the crystallinity of the cobalt carbonate sample was tested by XRD and was 54.62%.

[0063] (2) The filter cake obtained in step (1) is placed in a flash dryer for drying and sintering to obtain pre-sintered cobalt carbonate; the inlet air temperature of the flash dryer is set to 300° C., the outlet air temperature is set to 150° C., the main engine speed is set to 20 Hz, and the feed frequency is set to 10 Hz.

[0064] (3) The pre-sintered cobalt carbonate obtained in step (2) is put into a rotary kiln for calcination to obtain cobalt tetroxide; the feeding frequency is set to 3 Hz, the furnace tube rotation frequency is set to 12 Hz, the material residence time in the furnace tube is set to 3 h, and the calcination temperature is set to 710° C.

[0065] Instructions attached Figure 1 This is the cobalt tetroxide prepared in Example 1. As can be seen from the figure, the cobalt tetroxide particles have good dispersibility, uniform primary particle size, and narrow particle size distribution.

[0066] Example 2 A method for preparing cobalt trioxide comprises the following steps: (1) 200 L of 2.0 mol / L ammonium bicarbonate solution was added to a reactor as a base liquid, and a 2.5 mol / L cobalt sulfate solution was added to the reactor at a rate of 25 L / h and a 2.0 mol / L ammonium bicarbonate solution was added to the reactor at a rate of 30 L / h, and stirring was started and the speed was adjusted to 200 rpm, and the temperature was adjusted to 48°C for reaction; when the material in the reactor reached the upper limit, the addition and stirring were stopped, and the material was allowed to stand until the material was completely settled; a supernatant equivalent to half of the reactor cavity volume was extracted; then the cobalt sulfate solution and ammonium bicarbonate solution were added to the reactor in parallel and stirring was started for reaction, and the above-mentioned standing, extraction of part of the supernatant, and feeding operations were repeated 12 times to obtain cobalt carbonate with a median particle size Dv50 of 6.2 μm; the cobalt carbonate was filtered in a centrifuge and washed with pure water 3 times to obtain a filter cake; the crystallinity of the cobalt carbonate sample was tested by XRD and was 64.85%.

[0067] (2) The filter cake obtained in step (1) is placed in a flash dryer for drying and sintering to obtain pre-sintered cobalt carbonate; the inlet air temperature of the flash dryer is set to 400° C., the outlet air temperature is set to 180° C., the main engine speed is set to 30 Hz, and the feed frequency is set to 20 Hz.

[0068] (3) The pre-sintered cobalt carbonate obtained in step (2) is put into a rotary kiln for calcination to obtain cobalt tetroxide; the feeding frequency is set to 9 Hz, the furnace tube rotation frequency is set to 15 Hz, the material residence time in the furnace tube is set to 5 h, and the calcination temperature is set to 730° C.

[0069] Example 3 (1) 120 L of 3 mol / L potassium carbonate solution was added to a reactor as a base liquid, and a 2.2 mol / L cobalt sulfate solution was added to the reactor at a rate of 40 L / h and a 3 mol / L potassium carbonate solution was added to the reactor in parallel at a rate of 20 L / h, and stirring was started and the speed was adjusted to 260 rpm, and the temperature was adjusted to 55°C for reaction; when the material in the reactor reached the upper limit, the addition and stirring were stopped, and the material was allowed to stand until the material was completely settled; a supernatant equivalent to half of the reactor cavity volume was extracted; then the above cobalt sulfate solution and potassium carbonate solution were continued to be added in parallel and stirring was started for reaction, and the above standing, extracting part of the supernatant, and adding materials were repeated 13 times to obtain cobalt carbonate with a median particle size Dv50 of 6.9 μm; the cobalt carbonate was filtered in a centrifuge and washed with pure water 3 times to obtain a filter cake; the crystallinity of the cobalt carbonate sample was tested by XRD and was 76.63%.

[0070] (2) The filter cake obtained in step (1) is placed in a flash dryer for drying and sintering to obtain pre-sintered cobalt carbonate; the inlet air temperature of the flash dryer is set to 380° C., the outlet air temperature is set to 170° C., the main engine speed is set to 26 Hz, and the feed frequency is set to 12 Hz.

[0071] (3) The pre-sintered cobalt carbonate obtained in step (2) is put into a rotary kiln for calcination to obtain cobalt tetroxide; the feeding frequency is set to 5 Hz, the furnace tube rotation frequency is set to 12 Hz, the material residence time in the furnace tube is set to 3.5 h, and the calcination temperature is set to 720° C.

[0072] Example 4 (1) 160 L of 2.6 mol / L sodium bicarbonate solution was added to a reactor as a base liquid, and a 2.3 mol / L cobalt nitrate solution was added to the reactor at a rate of 30 L / h and a 2.6 mol / L sodium bicarbonate solution was added to the reactor at a rate of 28 L / h in parallel, and stirring was started and the speed was adjusted to 220 rpm, and the temperature was adjusted to 43°C for reaction; when the material in the reactor reached the upper limit, the addition and stirring were stopped, and the material was allowed to stand until the material was completely settled; a supernatant equivalent to half of the reactor cavity volume was extracted; then the above cobalt nitrate solution and sodium bicarbonate solution were continued to be added in parallel and stirring was started for reaction, and the above standing, extracting part of the supernatant, and adding were repeated 9 times to obtain cobalt carbonate with a median particle size Dv50 of 4.2 μm; the cobalt carbonate was filtered in a centrifuge and washed with pure water 3 times to obtain a filter cake; the crystallinity of the cobalt carbonate sample was tested by XRD and was 58.71%.

[0073] Steps (2) to (3) are the same as those in Example 1.

[0074] Example 5 The difference from Example 1 is that in step (3), the feed frequency is set to 9 Hz, the furnace tube rotation frequency is set to 15 Hz, the residence time of the material in the furnace tube is set to 5 h, and the calcination temperature is set to 730°C.

[0075] Example 6 (1) 100 L of 1.5 mol / L sodium carbonate solution was added to a reactor as a base liquid, and a 2.0 mol / L cobalt chloride solution was added to the reactor at a rate of 20 L / h and a 1.5 mol / L sodium carbonate solution was added to the reactor at a rate of 30 L / h, and stirring was started and the speed was adjusted to 200 rpm, and the temperature was adjusted to 40°C for reaction; when the material in the reactor reached the upper limit, the addition and stirring were stopped, and the material was allowed to stand until the material was completely settled; a supernatant equivalent to half of the reactor cavity volume was extracted; then the cobalt chloride solution and sodium carbonate solution were added to the reactor in parallel and stirring was started for reaction, and the above-mentioned standing, extraction of part of the supernatant, and feeding operations were repeated 20 times to obtain cobalt carbonate with a median particle size Dv50 of 18.8 μm; the cobalt carbonate was filtered in a centrifuge and washed with pure water 3 times to obtain a filter cake; the crystallinity of the cobalt carbonate sample was tested by XRD and was 30%.

[0076] (2) The filter cake obtained in step (1) is placed in a flash dryer for drying and sintering to obtain pre-sintered cobalt carbonate; the inlet air temperature of the flash dryer is set to 360° C., the outlet air temperature is set to 150° C., the main engine speed is set to 22 Hz, and the feed frequency is set to 13 Hz.

[0077] (3) The pre-sintered cobalt carbonate obtained in step (2) is put into a rotary kiln for calcination to obtain cobalt tetroxide; the feeding frequency is set to 3 Hz, the furnace tube rotation frequency is set to 12 Hz, the material residence time in the furnace tube is set to 3 h, and the calcination temperature is set to 740° C.

[0078] Instructions attached Figure 2 This is the cobalt tetroxide prepared in Example 6. As can be seen from the figure, the cobalt tetroxide particles have good dispersibility, uniform primary particle size, and narrow particle size distribution.

[0079] Example 7 (1) 100 L of 1.5 mol / L sodium carbonate solution was added to a reactor as a base liquid, and a 2.0 mol / L cobalt chloride solution was added to the reactor at a rate of 20 L / h and a 1.5 mol / L sodium carbonate solution was added to the reactor at a rate of 30 L / h, and stirring was started and the speed was adjusted to 200 rpm, and the temperature was adjusted to 45°C for reaction; when the material in the reactor reached the upper limit, the addition and stirring were stopped, and the material was allowed to stand until the material was completely settled; a supernatant equivalent to half of the reactor cavity volume was extracted; then the cobalt chloride solution and sodium carbonate solution were added to the reactor in parallel and stirring was started for reaction, and the above-mentioned standing, extraction of part of the supernatant, and feeding operations were repeated 22 times to obtain cobalt carbonate with a median particle size Dv50 of 21.0 μm; the cobalt carbonate was filtered in a centrifuge and washed with pure water 3 times to obtain a filter cake; the crystallinity of the cobalt carbonate sample was tested by XRD and was 45%.

[0080] Step (2) is the same as in Example 6.

[0081] (3) The pre-sintered cobalt carbonate obtained in step (2) is put into a rotary kiln for calcination to obtain cobalt tetroxide; the feeding frequency is set to 3 Hz, the furnace tube rotation frequency is set to 12 Hz, the material residence time in the furnace tube is set to 3 h, and the calcination temperature is set to 750° C.

[0082] Example 8 (1) 100 L of 1.5 mol / L sodium carbonate solution was added to a reactor as a base liquid, and a 2.0 mol / L cobalt chloride solution was added to the reactor at a rate of 20 L / h and a 1.5 mol / L sodium carbonate solution was added to the reactor at a rate of 30 L / h, and stirring was started and the speed was adjusted to 200 rpm, and the temperature was adjusted to 55°C for reaction; when the material in the reactor reached the upper limit, the addition and stirring were stopped, and the material was allowed to stand until the material was completely settled; a supernatant equivalent to half of the reactor cavity volume was extracted; then the cobalt chloride solution and sodium carbonate solution were added to the reactor in parallel and stirring was started for reaction, and the above-mentioned standing, extraction of part of the supernatant, and feeding operations were repeated 24 times to obtain cobalt carbonate with a median particle size Dv50 of 22.0 μm; the cobalt carbonate was filtered in a centrifuge and washed with pure water 3 times to obtain a filter cake; the crystallinity of the cobalt carbonate sample was tested by XRD and was 60%.

[0083] Step (2) is the same as in Example 6.

[0084] (3) The pre-sintered cobalt carbonate obtained in step (2) is put into a rotary kiln for calcination to obtain cobalt tetroxide; the feeding frequency is set to 3 Hz, the furnace tube rotation frequency is set to 12 Hz, the material residence time in the furnace tube is set to 3 h, and the calcination temperature is set to 760° C.

[0085] Comparative Example 1 The difference from Example 1 is that in step (2), the inlet air temperature of the flash dryer is set to 150° C., the outlet air temperature is set to 90° C., the main engine speed is set to 20 Hz, and the feed frequency is set to 10 Hz.

[0086] Instructions attached Figure 3 This is the cobalt tetroxide prepared in Comparative Example 1. It can be seen from the figure that larger agglomerates appear in the sample, and the surface morphology of the agglomerates is different from that of the dispersed particles, indicating that the particles have been over-burned and fused. The reason is that the fluidity of the agglomerated particles in the furnace tube has deteriorated and the heating is uneven.

[0087] Comparative Example 2 The difference from Example 1 is that in step (1), the reaction temperature is 60° C., the median particle size Dv50 of the obtained cobalt carbonate is 4.0 μm, and the crystallinity of the cobalt carbonate sample tested by XRD is 87.48%.

[0088] Instructions attached Figure 4 This is the cobalt tetroxide prepared in Comparative Example 2. It can be seen from the figure that there is powdering on the surface of the sample particles. The reason is that the grain size of the (111) crystal plane is too small, the particle bonding force is poor, and the surface structural stability of the material is poor.

[0089] Comparative Example 3 (1) 170 L of 2.4 mol / L sodium bicarbonate solution was added to the reactor as the base liquid, and 2.3 mol / L cobalt nitrate solution and 2.4 mol / L sodium bicarbonate solution were added to the reactor at a rate of 29 L / h and 26 L / h, respectively, and stirring was started and the speed was adjusted to 220 rpm, and the temperature was adjusted to 35°C for reaction; when the material in the reactor reached the upper limit, the addition and stirring were stopped, and the material was allowed to stand until the material was completely settled; a supernatant equivalent to half of the reactor cavity volume was extracted; then the cobalt nitrate solution and sodium bicarbonate solution were added in parallel and stirring was started for reaction, and the above-mentioned standing, extraction of part of the supernatant, and feeding operations were repeated 10 times to obtain cobalt carbonate with an average particle size of 4.2 μm; the cobalt carbonate was filtered in a centrifuge and washed with pure water 3 times to obtain a filter cake; the crystallinity of the cobalt carbonate sample was tested by XRD and was 43.61%.

[0090] Steps (2) to (3) are the same as those in Example 1.

[0091] Comparative Example 4 The difference from Example 6 is that the reaction temperature in step (1) is 60° C., and the crystallinity of the cobalt carbonate sample tested by XRD is 90.7%.

[0092] Comparative Example 5 The difference from Example 6 is that the reaction temperature in step (1) is 33° C., and the crystallinity of the cobalt carbonate sample tested by XRD is 25.6%.

[0093] The physical parameters and properties of the cobalt tetroxide prepared in the examples of the present invention and the comparative examples are shown in Table 1 and Table 2.

[0094] Table 1

[0095] Table 2

[0096] From the data in the table, it can be seen that the cobalt tetraoxide prepared in the comparative example does not meet the 3.33 μm 3 / g≤ ≤6.90μm 3 / g, so the specific capacity of the lithium cobalt oxide prepared by it is worse than that of the embodiment, indicating that maintaining the numerical relationship between BET, Dv50 and D(111) of cobalt oxide at a reasonable level is conducive to obtaining cobalt oxide with high mechanical properties and good electrochemical properties. Less than 3.33μm 3 / g, although the ΔD% of the obtained cobalt tetroxide is low (i.e., the mechanical properties are better), it is easy to cause uneven particle size distribution of the product. Therefore, the broadening coefficient of comparative examples 1, 3, and 5 is large, and due to the small BET, the lithium diffusion efficiency of the lithium cobalt oxide prepared therefrom is reduced, thereby reducing the specific capacity.

[0097] Comparative Examples 2 and 4 Above 6.90μm 3 / g, so its ΔD% is much larger than that in the embodiment. Due to the poor mechanical properties, the material is easily broken and powdered during the subsequent preparation of lithium cobalt oxide, resulting in a too wide particle size distribution of the obtained lithium cobalt oxide, thereby reducing its specific capacity.

[0098] Example 2 =0.1978μm 2 , Comparative Example 1 =0.1935μm 2 However, since the material particles of Example 2 are more dispersed, they have a higher BET, so they meet the 3.33 μm 3 / g≤ ≤6.90μm 3 / g, taking into account good mechanical strength and sintering activity, so the specific capacity of the obtained positive electrode material is large, which shows that the numerical relationship among BET, Dv50 and D(111) is maintained at a reasonable level, which is conducive to obtaining cobalt tetroxide with high mechanical strength and good sintering activity.

[0099] By comparing Examples 1 and 4 with Comparative Examples 2 and 3, it can be seen that by adjusting the process parameters for preparing cobalt carbonate, cobalt carbonate with different crystallinity can be obtained. From the data analysis in Table 1, it can be seen that cobalt carbonate with different crystallinity has an important influence on the grain size of the (111) crystal plane of the final product cobalt tetroxide. Specifically, the higher the crystallinity of cobalt carbonate, the smaller the grain size of the (111) crystal plane of cobalt tetroxide. The reason is that when the crystallinity of cobalt carbonate is high, it has a more regular crystal structure, the interface energy is reduced, and it is conducive to the formation of fine cobalt tetroxide grains during sintering, thereby reducing the grain size of the (111) crystal plane.

[0100] Comparison between Examples 1 and 5 shows that the calcination process conditions have an impact on the grain size of the (111) crystal plane of cobalt oxide. The reason is that the higher the calcination temperature and the longer the calcination time, the more time and energy there is for grain growth and development, and the larger the grain size, and vice versa.

[0101] From the comparison between Example 1 and Comparative Example 1, it can be seen that the process conditions of flash drying have an impact on the particle size, agglomeration degree, and grain size of the (111) crystal plane of cobalt tetroxide. The reason is that when the flash evaporation temperature is low, there is only a drying effect, and the agglomeration and particle size of cobalt carbonate do not change. When the flash evaporation temperature is high, in addition to drying and dehydration, cobalt carbonate also undergoes an oxidative decomposition reaction; further, since Comparative Example 1 has an agglomerated structure and its grain size of the (111) crystal plane is higher than that of Example 1, its specific capacity is lower.

[0102] Example 9 (1) 138 L of 2.4 mol / L ammonium bicarbonate solution was added to a reactor as a base liquid, and a 2.0 mol / L cobalt nitrate solution was added to the reactor at a rate of 20 L / h and a 2.4 mol / L ammonium bicarbonate solution was added to the reactor at a rate of 25 L / h in parallel, and stirring was started and the speed was adjusted to 276 rpm, and the temperature was adjusted to 41°C for reaction; when the material in the reactor reached the upper limit, the addition and stirring were stopped, and the material was allowed to stand until the material was completely settled; a supernatant equivalent to half of the reactor cavity volume was extracted; then the above cobalt nitrate solution and ammonium bicarbonate solution were continued to be added in parallel and stirring was started for reaction, and the above standing, extracting part of the supernatant, and adding materials were repeated 10 times to obtain cobalt carbonate with a median particle size Dv50 of 7.8 μm; the cobalt carbonate was filtered in a centrifuge and washed with pure water 3 times to obtain a filter cake; the crystallinity of the cobalt carbonate sample was tested by XRD and was 57.1%.

[0103] Steps (2) to (3) are the same as those in Example 3.

[0104] Example 10 (1) 124 L of 2.5 mol / L sodium bicarbonate solution was added to the reactor as the base liquid, and 2.2 mol / L cobalt nitrate solution was added to the reactor at a rate of 35 L / h and 2.5 mol / L sodium bicarbonate solution was added to the reactor at a rate of 29 L / h. At the same time, stirring was started and the speed was adjusted to 220 rpm, and the temperature was adjusted to 46 °C for reaction. When the material in the reactor reached the upper limit, the addition and stirring were stopped, and the material was allowed to stand until the material was completely settled. The supernatant equivalent to half of the reactor cavity volume was extracted. Then, the cobalt nitrate solution and sodium bicarbonate solution were added in parallel and stirring was started for reaction. After repeating the above-mentioned standing, extracting part of the supernatant, and adding materials for 14 times, cobalt carbonate with a median particle size Dv50 of 13.9 μm was obtained. The cobalt carbonate was filtered in a centrifuge and washed with pure water for 3 times to obtain a filter cake. The crystallinity of the cobalt carbonate sample was tested by XRD and was 52.3%.

[0105] Step (2) is the same as Example 6. (3) The pre-sintered cobalt carbonate obtained in step (2) is put into a rotary kiln for calcination to obtain cobalt tetroxide; the feeding frequency is set to 6 Hz, the furnace tube rotation frequency is set to 14 Hz, the material residence time in the furnace tube is set to 3 h, and the calcination temperature is set to 740°C.

[0106] Embodiment 11 (1) 136 L of 1.2 mol / L ammonium bicarbonate solution was added to a reactor as a base liquid, and a 2.0 mol / L cobalt chloride solution was added to the reactor at a rate of 25 L / h and a 1.2 mol / L ammonium bicarbonate solution was added to the reactor at a rate of 23 L / h. At the same time, stirring was started and the speed was adjusted to 240 rpm, and the temperature was adjusted to 51°C for reaction; when the material in the reactor reached the upper limit, the addition and stirring were stopped, and the material was allowed to stand until the material was completely settled; a supernatant equivalent to half of the reactor cavity volume was extracted; then the above cobalt chloride solution and sodium carbonate solution were added in parallel and stirring was started for reaction, and the above standing, extracting part of the supernatant, and adding were repeated 21 times to obtain cobalt carbonate with a median particle size Dv50 of 21.9 μm; the cobalt carbonate was filtered in a centrifuge and washed with pure water 3 times to obtain a filter cake; the crystallinity of the cobalt carbonate sample was tested by XRD and was 65%.

[0107] Step (2) is the same as in Example 6.

[0108] (3) The pre-sintered cobalt carbonate obtained in step (2) is put into a rotary kiln for calcination to obtain cobalt tetroxide; the feeding frequency is set to 4 Hz, the furnace tube rotation frequency is set to 15 Hz, the material residence time in the furnace tube is set to 4.5 h, and the calcination temperature is set to 755° C.

[0109] The physical parameters of the cobalt tetroxide prepared in Examples 9-11 are shown in Table 3.

[0110] Table 3

[0111] From the data in Table 3, it can be seen that the preparation method provided by the present invention can produce a Dv50 of 3~20μm and meet the requirements of 3.33μm. 3 / g≤ ≤6.90μm 3 / g of cobalt tetroxide, the cobalt tetroxide has a low particle size broadening coefficient and good mechanical properties.

[0112] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A cobalt tetraoxide, It is characterized in that The Dv50, the grain size D(111) of the (111) crystal plane, and the specific surface area BET of the cobalt tetraoxide satisfy the following relationship: 3.33 μm 3 / g≤ ≤6.90μm 3 / g, wherein the Dv50 of the cobalt tetraoxide is 3-20 μm, Dv50 refers to the particle size corresponding to 50% of the cumulative particle size distribution based on volume statistics, and the unit of BET is m 2 / g, the unit of D(111) is μm, The unit is μm 3 .

2. A cobalt tetraoxide according to claim 1, It is characterized in that The grain size D(111) of the cobalt oxide (111) crystal plane is 0.0450-0.0510 μm or 0.0560-0.0680 μm; Or / and, the specific surface area of ​​the cobalt tetraoxide is 2 to 6.5 m 2 / g; Or / and, the particle size broadening coefficient Span of the cobalt oxide is less than 1, wherein Span=(Dv90-Dv10) / Dv50, Dv10, Dv50, and Dv90 refer to the particle sizes corresponding to 10%, 50%, and 90% of the cumulative particle size distribution based on volume statistics; or / and, the change rate of Dv50 of the cobalt oxide after 7500N pressing relative to that before pressing Less than 2.0%.

3. Cobalt tetraoxide according to claim 1 or 2, It is characterized in that The grain size D(111) of the (111) crystal plane of the cobalt oxide is 0.0450-0.0510 μm, and the median particle size Dv50 is 3-6 μm.

4. The method for preparing cobalt tetraoxide according to any one of claims 1 to 3, It is characterized in that The cobalt trioxide is obtained by pre-sintering and calcining cobalt carbonate with a crystallinity of 30% to 80% and a median particle size Dv50 of 3 to 22 μm.

5. The method for preparing cobalt trioxide according to claim 4, It is characterized in that The preparation method of cobalt carbonate is as follows: adding a cobalt salt solution and a precipitant solution to a reactor containing a bottom liquid in parallel, and stirring is started to react at the same time, when the material in the reactor reaches the upper limit, the material is allowed to stand for sedimentation, and part of the supernatant is extracted, and the above-mentioned operations of adding, stirring, standing, and extracting part of the supernatant are repeated until the obtained cobalt carbonate reaches the target particle size, and the solid is taken for washing after solid-liquid separation.

6. The method for preparing cobalt trioxide according to claim 5, It is characterized in that The method for preparing cobalt carbonate further includes at least one of the following features: Feature 1: The cobalt salt in the cobalt salt solution is at least one of cobalt chloride, cobalt sulfate and cobalt nitrate, and the concentration of the cobalt salt solution is 2.0-2.5 mol / L; Feature 2: The precipitant in the precipitant solution is at least one of sodium carbonate, sodium bicarbonate, ammonium bicarbonate and potassium carbonate, and the concentration of the precipitant solution is 1.0-3.0 mol / L; Feature 3: The flow rate of adding the cobalt salt solution is 20-40 L / h, and the flow rate of adding the precipitant solution is 20-30 L / h; Feature 4: The base liquid is the precipitant solution; Feature 5: The stirring speed is 200-300 rpm, and the reaction temperature is 40-55°C; Feature 6: Extracting part of the supernatant means extracting a portion of the supernatant equivalent to half of the volume of the reactor chamber; Feature 7: The target particle size refers to the median particle size Dv50 of cobalt carbonate being 3 to 22 μm.

7. The method for preparing cobalt tetraoxide according to claim 4, It is characterized in that The pre-sintering adopts a flash dryer, the air inlet temperature of the flash dryer is 300-400°C, the air outlet temperature is 150-180°C, the main engine speed is 20-30Hz, and the feed frequency is 10-20Hz; Or / and, the calcination is carried out in a rotary kiln, the feeding frequency of the rotary kiln is 3-9 Hz, the rotation frequency of the furnace tube is 12-15 Hz, the temperature is 710-760° C., and the calcination time is 3-5 hours.

8. A lithium cobalt oxide, It is characterized in that The lithium cobalt oxide is obtained by mixing the cobalt trioxide described in any one of claims 1 to 3 with a lithium source and sintering them.

9. A positive electrode sheet, It is characterized in that The positive electrode plate comprises the lithium cobalt oxide as claimed in claim 8.

10. A battery, It is characterized in that The battery comprises the positive electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Preparation method of large-particle-size and high-density spherical cobalt oxide

    CN105399148A

  • Preparation method of compact crystal form cobaltosic oxide

    CN106882843A

  • Cobalt oxide for lithium secondary battery, preparing method thereof, lithium cobalt oxide and lithium secondary battery

    CN107814417A

  • Doped cobaltosic oxide and preparation method thereof

    CN112760710A

  • Cobalt composite hydroxide and preparation method thereof, lithium ion battery positive electrode material and lithium ion battery

    CN114477311A

Cited By

  • Cobaltosic oxide and preparation method thereof

    CN120736568A

  • A tricobalt tetroxide and a preparation method thereof

    CN120736568B

  • Cobalt(ii,iii) oxide and preparation method therefor, lithium cobalt oxide, positive electrode sheet, and battery

    WO2026097955A1